Increased mobilization of mesenchymal stem cells in patients with acute respiratory distress syndrome undergoing extracorporeal membrane oxygenation - Patry, Christian; Doniga, Thalia; Lenz- van der Ham, Franziska; Viergutz, Tim; Weiß, Christel; Tönshoff, Burkhard; Kalenka, Armin; Yard, Benito A.; Krebs, Jörg; Schaible, Thomas; Beck, Grietje; Rafat, Neysan (PLOS ONE, 2020)
Background: The acute respiratory distress syndrome (ARDS) is characterized by pulmonary epithelial and endothelial barrier dysfunction and injury. In severe forms of ARDS, extracorporeal membrane oxygenation (ECMO) is often the last option for life support. Endothelial progenitor (EPC) and mesenchymal stem cells (MSC) can regenerate damaged endothelium and thereby improve pulmonary endothelial dysfunction. However, we still lack sufficient knowledge about how ECMO might affect EPC- and MSC-mediated regenerative pathways in ARDS. Therefore, we investigated if ECMO impacts EPC and MSC numbers in ARDS patients. Methods: Peripheral blood mononuclear cells from ARDS patients undergoing ECMO (n = 16) and without ECMO support (n = 12) and from healthy volunteers (n = 16) were isolated. The number and presence of circulating EPC and MSC was detected by flow cytometry. Serum concentrations of vascular endothelial growth factor (VEGF) and angiopoietin 2 (Ang2) were determined. Results: In the ECMO group, MSC subpopulations were higher by 71% compared to the non-ECMO group. Numbers of circulating EPC were not significantly altered. During ECMO, VEGF and Ang2 serum levels remained unchanged compared to the non-ECMO group (p = 0.16), but Ang2 serum levels in non-survivors of ARDS were significantly increased by 100% (p = 0.02) compared to survivors. Conclusions: ECMO support in ARDS is specifically associated with an increased number of circulating MSC, most likely due to enhanced mobilization, but not with a higher numbers of EPC or serum concentrations of VEGF and Ang2.
Gesehen am 07.10.2020